Technical efficiency and its determinants in the Gambia secondary health care service delivery - Jarjue, Gibril (2014)
The amount of resources the Gambia government allocate for health care service delivery has given rise to a huge interest on how the Gambia health system is performing. This rise in interest is due to the fact that government wants to maximize the use of the existing scarce health resources. The Gambia like any other developing country is vulnerable to the emergence and re-emergence of diseases which may seriously affects the functionality of the entire health system. For this reason, this research is conducted to investigate the Technical Efficiency and its Determinants in the Gambia Secondary Healthcare Service Delivery. This is because the secondary health care service delivery system of the Gambia is most of the time the first point of contact for many patients across the country irrespective of their social status and comprised of 41 health centers country wide. Furthermore, its close proximity to remote villages and towns makes it a suitable choice for people to rely on for cheaper healthcare. The study employs three basic methodologies which are Output-oriented Data Envelopment Analysis (DEA), Bootstrapping and Tobit regression methodologies. However, to be more specific, this study uses output-oriented DEA method under Variable Return to Scale assumption. DEA is a nonparametric technique which identifies best practice within a given sample of firms and measures efficiency based on the differences between the determined DEA score and best practice score, and is used to measure technical efficiency. The results of this study reveals that out of the forty one (41) health centers, only 9 (22%) health centers are technically efficient according to DEA method while all health centers are inefficient according to bootstrap method. The mean technical efficiency score according to the study is 0.65 under DEA and 0.55 for bootstrapping. Apparently, West Coast 1 health region out-performs all other health regions during the study with an average efficiency score of 0.92. Interestingly, factors such as bed occupancy ratio, inpatient staff and outpatient staff ratio are reported to be highly significant and are also the main determinants of efficiency in the Gambian secondary health care service delivery system. Thus the results from the study show the need to improve efficiency level through health care service delivery in Gambia health system.